Renal Artery Resistive Index and Estimated Glomerular Filtration Rate in Patients with Non-alcoholic Fatty Liver Disease - Aksu, Yusuf; Uslu, Ali Ugur; Tarhan, Gulten; Tiryaki, Şaban (Current Medical Imaging, 2022)
Objective: Non-alcoholic fatty liver disease (NAFLD) may affect many organs and systems, especially the kidney as well as the liver. While NAFLD’s renal impacts can be evaluated via the estimated glomerular filtration rate (eGFR), its effects on renal hemodynamic changes can be monitored with the renal resistive index (RRI). Our aim in this study is to evaluate RRI and eGFR in NAFLD patients. Materials and Methods: In this study, a total of 69 patients with NAFLD and 50 age- and gendermatched healthy controls were included. The basic clinical and laboratory parameters of patient and control groups were assessed and recorded. Results: In the patient group, the RRI was observed as 0.64±0.06 and eGFR value as 86±52 (mL/min/1.73m2), while in the control group, the RRI was 0.61±0.05 and eGFR was 95.40±20.21 (mL/min/1.73m2). Compared to the control group, the RRI and eGFR values were significantly different in the patient group (PRRI=0.003 and PeGFR=0.025). There was a negative correlation observed between the RRI and eGFR (r=-0.347, P=0.003). Receiver-operating characteristic curve analysis suggested that the optimum RRI cut-off value for patients with NAFLD is 0.62, with 65% sensitivity and 60% specificity (p=0.002). There was an independent relationship found between the RRI and eGFR according to the linear regression analysis (β=-0.301, P=0.015). Conclusion: This study shows that RRI may be an indicator of renal functions, such as eGFR in patients with NAFLD.
Keywords: kidney